Emergency Department Visits for Food Allergy in Taiwan: A Retrospective Study - Chan-Fai Chan; Po-Hon Chen; Ching-Feng Huang; Tzee-Chung Wu (Pediatrics and Neonatology)
Little is known about the characteristics of patients who visit the emergency department (ED) due to food allergy in Taiwan. This study aims to assess the triggers, clinical presentations, and management of patients presenting to a tertiary ED for food allergy. Methods: This is a retrospective study of 369 visits presenting to the ED of Taipei Veterans General Hospital, Taipei, Taiwan for food allergy over a 2 year period. Patients' demographics, food allergens, presenting features, and management were addressed and analyzed. Adult and pediatric cases were also compared. Results: The patients had an average age of 32.9 years [standard deviation (SD) ± 20.6]; the cohort was 66.9% adult and 53.7% male. Seafood (67.5%), fish (6.2%), and fruits (4.3%) were the major foods eliciting acute allergic reactions. Overall itchy mucocutaneous lesion was the most common presentation (85.6%), followed by anaphylaxis (12.2%), respiratory distress (1.4%), and anaphylactic shock (0.8%). Mucocutaneous involvement was more common in the pediatric population (92.6% vs. 82.2%, p = 0.007), whereas anaphylaxis was more prevalent in adults (15.4% vs. 5.7%, p = 0.0068). Antihistamines (98.6%) and systemic corticosteroids (63.1%) were commonly used medications. Only 2.2% of patients with anaphylaxis received epinephrine. The average duration in the ED was 1.6 hours (SD ± 1.8). No death was documented in the current study. Conclusion: Seafood, fish, and fruits are common foods which cause acute allergic reactions in Taiwan. Although most food allergies are mild, anaphylactic shock still presents in about 1% of patients. Only a minority of patients with anaphylaxis receive epinephrine. As anaphylaxis may be life-threatening, prompt education and use of an epinephrine auto-injector deserves further concern.